2017
DOI: 10.1093/cid/cix661
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth Associated With Group B Streptococcus Maternal Colonization Worldwide: Systematic Review and Meta-analyses

Abstract: Complications of preterm birth are the leading cause of deaths in children aged <5 years. Group B Streptococcus may be a preventable and important contributor to this burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
128
3
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 63 publications
1
128
3
5
Order By: Relevance
“…As expected, the percentage of self-reported treatment for vaginal discharge was much higher than that in patient medical records. The prevalence of vaginal discharge in our study was much higher than those previously reported (16), and we could not assess the pathogen associated with infection. Another study conducted elsewhere reported that vulvovaginal candidiasis was the most prevalent cause of vaginal discharge (17).…”
Section: ' Discussioncontrasting
confidence: 89%
“…As expected, the percentage of self-reported treatment for vaginal discharge was much higher than that in patient medical records. The prevalence of vaginal discharge in our study was much higher than those previously reported (16), and we could not assess the pathogen associated with infection. Another study conducted elsewhere reported that vulvovaginal candidiasis was the most prevalent cause of vaginal discharge (17).…”
Section: ' Discussioncontrasting
confidence: 89%
“…9,52 Notably, these infants are at much higher risk of EOGBS disease as well as GBS-related mortality. 53 For this reason, the CDC has suggested that most preterm deliveries be accompanied by IAP. However, more research towards best IAP management for women delivering preterm is needed, as long-term exposure to antibiotics poses a risk for preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Infant invasive GBS disease is classified as early-onset disease (EOD) if it occurs during the first 6 days of life or late-onset disease (LOD) if it develops 7 or more days after birth. The worldwide burden of infant and maternal GBS disease is substantial, [4][5][6][7][8][9][10][11][12][13] and efforts are under-way to develop vaccines as a preventive measure to replace or supplement antenatal screening and intrapartum antibiotics effective against early but not late-onset disease. [14][15][16][17] EOD arises from vertical transmission from a GBS colonized mother to her baby during or just before birth, with clinical signs occurring within 48 h in more than 90% of cases.…”
Section: Introductionmentioning
confidence: 99%